INTEGRASI TEKNOLOGI PADA PEMBELAJARAN MATEMATIKA SECARA DARING DI SMA BERDASARKAN MODEL SAMR (SUBSTITUSI, AUGMENTASI, MODIFIKASI, DAN REDEFINISI) - Siti Silmi Kaafah; Isna Rafianti (INSPIRAMATIKA, 2022)
This research was motivated by the learning of mathematics during the Covid-19 pandemic which was carried out online with the help of technology applied by teachers to students in the learning process. The aim of the research is to find out and describe the integration of technology that has been applied by teachers in online mathematics learning in high schools based on the stages of the SAMR model. The design of this research is a qualitative research with a descriptive research method used to provide an overview or description and find out about the integration of technology based on the SAMR model in online mathematics learning. From this study it was found that this high school school has implemented technology integration during the online mathematics learning process based on the SAMR model. In its overall application, mathematics subject teachers in SMA are already at the redefinition stage with intensity sometimes at each stage. From this statement, seen also from the student's point of view, the results obtained are in accordance with the teacher that it is already at the redefinition stage, even though in its implementation there are inhibiting and supporting factors. Obstacles and students' desires in exploring the learning technology used during online mathematics learning. The conclusion from this study is that on the whole the teachers at the SMA have implemented technology integration at every stage of the SAMR model, already at the redefinition stage between teacher and students.